Discovery of New D‐Ring Modified Isosteviol Derivatives as Potent Cardioprotective Agents against Oxidative Stress‐Trigged Damage. Issue 4 (23rd March 2023) - Chen, Zhenyu; Xu, Ruilong; Jia, Qi; Xu, Xiaojia; Li, Dehuai; Li, Zhiyin; Luo, Liping; Zhao, Yu
Abstract: Cardiovascular diseases (CVDs) are a major global health concern, and oxidative stress is known to play a central role in their pathogenesis. The identification of new agents capable of inhibiting oxidative stress presents a promising strategy for preventing and treating CVDs. Natural products and their derivatives offer a valuable source for drug discovery, and isosteviol, a readily available natural product, is known to exhibit cardioprotective effects. In this study, 22 new D‐ring modified isosteviol derivatives were synthesized and evaluated for their cardioprotective effect in vivo using the zebrafish cardiomyopathy model. The findings revealed that derivative 4e exhibited the most potent cardioprotective effect, surpassing its parent compound isosteviol and the positive drug levosimendan. At 1 μM, derivative 4e significantly protected the cardiomyocytes from injury, while at 10 μM it effectively maintained normal heart phenotypes, preventing cardiac dysfunction in zebrafish. Further investigation demonstrated that 4e protected cardiomyocytes from oxidative stress‐induced damage by inhibiting reactive oxygen species overaccumulation, activating superoxide dismutase 2 expression, and enhancing the endogenous antioxidant defense system. These results suggest that isosteviol derivatives, particularly 4e, have the potential to serve as a novel class of cardioprotective agents for the prevention and treatment of CVDs. Abstract :